2012
DOI: 10.1002/adma.201201361
|View full text |Cite
|
Sign up to set email alerts
|

GaS and GaSe Ultrathin Layer Transistors

Abstract: Room-temperature, bottom-gate, field-effect transistor characteristics of 2D ultrathin layer GaS and GaSe prepared from the bulk crystals using a micromechanical cleavage technique are reported. The transistors based on active GaS and GaSe ultrathin layers demonstrate typical n-and p-type conductance transistor operation along with a good ON/OFF ratio and electron differential mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
475
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(496 citation statements)
references
References 41 publications
16
475
1
4
Order By: Relevance
“…Because of this merit, Few layered 2DLMCs such as transition metal dichalcogenides (TMDs) (MoS 2 ,26, 27, 28 WS 2 ,29, 30, 31, 32, 33, 34, 35, 36 TiS 3 ,37 etc.) and group III–VI nanomaterials (InSe,38, 39, 40, 41, 42 GaSe,43, 44, 45, 46, 47, 48 etc.) have been extensively investigated in many fields including photodetectors,49, 50, 51, 52, 53, 54, 55, 56, 57, 58 gas sensors,59, 60 field effect transistors (FETs),38, 61, 62, 63, 64, 65 and flexible devices 66, 67, 68…”
Section: Introductionmentioning
confidence: 99%
“…Because of this merit, Few layered 2DLMCs such as transition metal dichalcogenides (TMDs) (MoS 2 ,26, 27, 28 WS 2 ,29, 30, 31, 32, 33, 34, 35, 36 TiS 3 ,37 etc.) and group III–VI nanomaterials (InSe,38, 39, 40, 41, 42 GaSe,43, 44, 45, 46, 47, 48 etc.) have been extensively investigated in many fields including photodetectors,49, 50, 51, 52, 53, 54, 55, 56, 57, 58 gas sensors,59, 60 field effect transistors (FETs),38, 61, 62, 63, 64, 65 and flexible devices 66, 67, 68…”
Section: Introductionmentioning
confidence: 99%
“…In addition to graphene, other 2D crystals such as germanene, 2,3 silicene, 4,5 stanene, 6,7 transition-metal dichalcogenides (TMDs), [8][9][10][11][12] and post-transitionmetal chalcogenides (TMCs) [13][14][15] have been predicted and successfully synthesized. One of the most prominent members of 2D crystals is MoS 2 .…”
Section: Discovery Of Graphenementioning
confidence: 99%
“…Experimental studies have demonstrated synthesis of monolayers and or few layers of GaS, GaSe and InSe thin films. 10,[14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%